Bahasa dalam Perspektif Pengembangan Moralitas Kepemimpinan - Muda, Lisdawati (IAIN Sultan Amai Gorontalo, 2015)
A leader is a man who has good knowledge and good skill; he is able to persuade others to do something together and to gain a goal. A leader is the individual who has talent; has power and authority to manage and to to direct his staffs or his followers. Leading does not ignore collaboration, because it must give chance to others to do the duties. A leader who has good morality should equip hisself with the terms which called three senses namely kindness, dedication, and neutrality. He also should have five moralities as the main aspect, namely wisdom, kindness, honesty, braveness, and diciplines. Leadership related to attitude and behaviour, logic intellectual and emotional mature, ability and skill. The skill of communication is an important element in implementing leadership activities. The quality is signed by the good communication between leader and his staffs or his followers, with usingÂ the good and the contextual language.